Analysis of Behavioural of the 5M Messages (Using Masks, Keeping Distance, Washing Hands, Avoiding Crowds and Limiting Mobility) during Covid 19: A Study of the Perspective of Hermeunetics Theory - Ali, Muhammad; Mursalin, M; Putri, Rahma Atiya (Management Research and Behavior Journal, 2023)
This study was motivated by problems and unrest against the number of cases of victims exposed to COVID-19 increased during the Covid-19 Pandemic period. In this study, the authors analyzed five banner texts that focused on the appeal on how to minimize the spread of COVID-19. This study aims to determine messages related to how to overcome the application of the application of 5 M application found in banners, benner, and community service advertisements. As well as the meaning contained in the text of the 5 M application message about Covid-19. Data collection techniques with library research or library research with a hermeneutics approach. This thesis uses hermeneutics theory Hans-Georg Gadamer. With this hermenetuika theory, a message of 5 m is found through historical, dialectics and application. The results of this study indicate that in the text found a message related to the application of 5 m, namely the distribution of messages invites the public to comply with the things that have been determined by the government about the dangers of Covid-19, containing relevant sentences that cause close relationships and relationships related to the problem being faced in the middle public. In receiving a message it needs to be considered related to the truth of the message itself. Given that a message that is not clear truth can lead to chaos and the increasing number of Covid-19 cases among the people. Thus, researchers also suggest that people always do a message of application of 5 M that has been implemented by the government.